Design optimisation of adaptive head lights. (2021) - Palanivendhan, M.; Joshuapaul, E.; Chandradass, J.; Philip, Jennifer; Aaftaab Ahmed, Mohammed
Abstract: This work aims to conduct an extensive research on the working of the adaptive headlamps and its ability to function efficiently to enhance stress free driving. What we have done is we have meticulously integrated the steering wheel and the headlamp with the help of certain components such as frame structure, spur gears, ten-turn potentiometer and motor. We have incorporated Fuzzy logic, using C programming to this, the code used in the micro controller is based on this software to provide a more stable and smooth turning of the headlamps while the steering wheel is being moved either sides. We've added a feature where there is an automatic reduction in the intensity of the headlight when there is enough light to illuminate the road is produced on the other end of the road, this way we aim to provide stress free driving to all the drivers out there. The ten-turn potentiometer will supply varying current, whose magnitude will be determined by the steering wheel angle. We have also provided a ease factor to prevent the irrational movement of the headlight by keeping them stationery for the first 30 degrees movement of the steering wheel on either sides. We claim that the advantage would be that there will be a considerable decrease in the number of road accidents caused during the night hours and provide stress free driving experience. This setup will efficiently gimmick an actually driving experience for better analysis and results.